2012
DOI: 10.1073/pnas.1210022110
|View full text |Cite|
|
Sign up to set email alerts
|

Increased lipolysis and altered lipid homeostasis protect γ-synuclein–null mutant mice from diet-induced obesity

Abstract: Synucleins are a family of homologous proteins principally known for their involvement in neurodegeneration. γ-Synuclein is highly expressed in human white adipose tissue and increased in obesity.Here we show that γ-synuclein is nutritionally regulated in white adipose tissue whereas its loss partially protects mice from high-fat diet (HFD)-induced obesity and ameliorates some of the associated metabolic complications. Compared with HFD-fed WT mice, HFD-fed γ-synuclein-null mutant mice display increased lipoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…Moreover, increased partitioning of SNAP23 to cytosolic/microsomal compartments and reduced SNAP23 expression at the plasma membrane was also observed in studies using muscle cells of type-2 diabetic patients [69]. In keeping with this, it was recently demonstrated that α-synuclein null mice that are resistance to diet induced obesity showed decreased lipid droplet size because of reduced SNARE complex formation in adipocytes, further highlighting the role of SNARE proteins in lipid droplet formation and fusion [70]. It should be noted however, another report revealed FSP27 and Plin1 interact with each other and are involved in the formation of unilocular lipid droplets [66].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, increased partitioning of SNAP23 to cytosolic/microsomal compartments and reduced SNAP23 expression at the plasma membrane was also observed in studies using muscle cells of type-2 diabetic patients [69]. In keeping with this, it was recently demonstrated that α-synuclein null mice that are resistance to diet induced obesity showed decreased lipid droplet size because of reduced SNARE complex formation in adipocytes, further highlighting the role of SNARE proteins in lipid droplet formation and fusion [70]. It should be noted however, another report revealed FSP27 and Plin1 interact with each other and are involved in the formation of unilocular lipid droplets [66].…”
Section: Discussionmentioning
confidence: 68%
“…γ synuclein is a protein that modulates synaptic trafficking in neurons but also lipid droplets generating intracellular fatty acids. Notably, the γ synuclein whole body knockout is protected against diet-induced obesity (Oort et al, 2008; Millership et al, 2012).
10.7554/eLife.06667.009Figure 4.NG gene expression in LXRs Nav mice vs control mice.( A ) Gene expression in NG from LXRs Nav and control mice fed with NC or WD.
…”
Section: Resultsmentioning
confidence: 99%
“…Outside the nervous system, this protein is abundant in white fat adipocytes, and the level of its expression correlates with the degree of obesity (36). Moreover, our latest study demonstrated the role of γ-synuclein in regulation of lipolysis and lipid droplet formation in adipocytes (37). In these cells, γ-synuclein is not associated with lipid droplets but potentiates translocation of cytosolic SNAP-23 to their surface, enhances triacylglyceride incorporation into lipid droplets, and increases their size at times of nutrient excess.…”
Section: Discussionmentioning
confidence: 99%